Pre-breeding behaviour affects condition, assessed by abdominal profile, and hence breeding success of Canada Geese Branta canadensis - Johnson, I P; Sibly, R M (Wildfowl, 1993)
A population of Canada Geese in southern England was studied in the pre-breeding and breeding seasons of 1983 and 1984, and abdominal profile (AP) was recorded as a measure of stored reserves. Female APs increased during the prebreeding period, and overall females had higher APs than males during this period. Having allowed for the effects of season and time of day, AP 50 days after 1 January (AP50) was calculated for each female to give an estimate of condition in the middle of the prebreeding period AP50 was correlated with % time feeding in the pre-breeding period, as expected since stored reserves were derived from processed food. Female AP50 also correlated with her mate’s size, as assessed by tarsal length, in accordance with the mate protection hypothesis, and females with higher AP50 nested earlier, as expected if breeding is contingent on the acquisition of sufficient stored reserves. Early nesting correlated with both hatching and fledging success. The simplest interpretation of our results is that breeding success was strongly influenced by the reserves acquired by the female, indicating there was a premium on effective feeding in the pre-breeding period, promoted as necessary by protection by her mate.